Genome‐wide SNP genotyping reveals hidden population structure of an acroporid species at a subtropical coral island: Implications for coral restoration. Issue 9 (21st June 2021) - Zayasu, Yuna; Takeuchi, Takeshi; Nagata, Tomofumi; Kanai, Megumi; Fujie, Manabu; Kawamitsu, Mayumi; Chinen, Wakana; Shinzato, Chuya; Satoh, Noriyuki
Abstract: It is essential to consider genetic composition for both conventional coral restoration management and for initiating new interventions to counter the significant global decline in living corals. Population genetic structure at a fine spatial scale should be carefully evaluated before implementing strategies to achieve self‐sustaining ecosystems via coral restoration. This study investigated the population genetic structure of two acroporid species at Kume Island, Okinawa, Japan. There were 140 colonies of Acropora digitifera collected from seven study sites, and 81 colonies of Acropora tenuis from six sites. In total, 384 single nucleotide polymorphism (SNP) loci for A. digitifera and 470 SNPs for A. tenuis were obtained using a comparatively economical technique, Multiplexed ISSR Genotyping by sequencing. Observed heterozygosity was significantly lower than expected heterozygosity at all SNP sites in both acroporid species, suggesting deficient genetic diversity possibly caused by past massive coral bleaching. Even though both species are broadcast spawners, the population structure was different in the two species. No detectable structure was evident in A. digitifera, but two distinct clades were found in A. tenuis . The genetic homogeneity of A. digitifera at Kume Island suggests that this species could be used as a focal species for active restoration in terms of genetic differentiation at this island. By contrast, A. tenuis unexpectedly included two distinct clades with little or no admixture within a small study area, possibly representing two reproductively isolated cryptic species. Thus, when using A. tenuis, it would be prudent to avoid disturbing the genetic composition of wild populations until this question is answered.